2022
DOI: 10.3390/ph15050527
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Accumulates in the Retina Following Chronic Systemic Administration

Abstract: Opioid transport into the central nervous system is crucial for the analgesic efficacy of opioid drugs. Thus, the pharmacokinetics of opioid analgesics such as morphine have been extensively studied in systemic circulation and the brain. While opioid metabolites are routinely detected in the vitreous fluid of the eye during postmortem toxicological analyses, the pharmacokinetics of morphine within the retina of the eye remains largely unexplored. In this study, we measured morphine in mouse retina following sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(38 citation statements)
references
References 81 publications
7
31
0
Order By: Relevance
“…Previous studies have also shown that opioids deposit in the mammalian retina/VH following systemic administration (Husain et al, 2012;Gottås et al, 2016;Maskell et al, 2016;Bergum et al, 2022). Recently, our group found that morphine similarly deposits in the mouse retina following systemic injection (Bergum et al, 2022). Surprisingly, our detailed study showed that retinal morphine levels greatly exceeded the concentrations detected in the hypothalamus (Figure 2).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Previous studies have also shown that opioids deposit in the mammalian retina/VH following systemic administration (Husain et al, 2012;Gottås et al, 2016;Maskell et al, 2016;Bergum et al, 2022). Recently, our group found that morphine similarly deposits in the mouse retina following systemic injection (Bergum et al, 2022). Surprisingly, our detailed study showed that retinal morphine levels greatly exceeded the concentrations detected in the hypothalamus (Figure 2).…”
Section: Discussionmentioning
confidence: 52%
“…Surprisingly, our detailed study showed that retinal morphine levels greatly exceeded the concentrations detected in the hypothalamus (Figure 2). In addition to this, we observed sustained increases in morphine levels in the retina compared to Graphical representation of the pharmacokinetic evidence for a retinal contribution to chronic opioid-induced sleep/wake disturbances (as presented in Bergum et al, 2022). Morphine levels in the retina appear to accumulate following chronic systemic exposure, while levels in both the serum and hypothalamus remain the same.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations